Impact Zone : The Battle of the DMZ in Vietnam, 1967-1968 - Brown, Jim, 1942- (Book collections on Project MUSE., 2004)
A Vietnam War combat memoir from the perspective of an artilleryman. Impact Zone documents Marine First Lieutenant James S. Brown's intense battle experiences, including those at Khe Sanh and Con Thien, throughout his thirteen months of service on the DMZ during 1967-68. This high-action account also reflects Brown's growing belief that the Vietnam War was mis-fought due to the unproductive political leadership of President Johnson and his administration. Brown's naivete developed into hardening skepticism and cynicism as he faced the harsh realities of war, thoug.